Cashew nut shell liquid effect on the corrosion behaviour of the metallic alloys - Pino Hernández, Carlos Andrés (Escuela Colombiana de Ingeniería, 2024)
Currently, CNSL is a wasted by-product from cashew transformation in Vichada, Colombia, with high potential in industries such as corrosion protection. This thesis pretends to explore potential applications in corrosion and tribocorrosion field of raw CNSL. This implies a mechanical extraction without chemical or thermal processes that could affect the oil composition. Three materials were chosen to conduct the research based on typical metals employed in agroindustry and food transformation sector: a mild steel, a martensitic stainless steel and commercial aluminium alloy. The anticorrosive use of CNSL was split in two ways, on one hand, as liquid inhibitor evaluated by electrochemistry and alternate immersion tests, then as lubricant by tribological experiments and under both conditions in tribocorrosion setup. The alternate immersion tests for active metal were omitted because the area reduction by material loss is evident, while depth of localised corrosion is not visible and could affect the traction properties of passive metals. The adsorption mechanism was not characterized due the intention of this work is, essentially, to explore diverse applications of CNSL in corrosion issues. On the other hand, CNSL was employed to form a polymerized organic film onto mild steel surface through 3X2 experiment design (3 temperatures along 2 times). Owing to the main concern is to contribute to the knowledge about the possibilities to give add-value to CNSL, the chemical, physical, electrochemical and tribocorrosion experiments were conducted to select the best parameters to obtain the organic coating based on literature and experimental results.
List of Figures List of Tables 1 INTRODUCTION 1.1 CONTEXT AND RATIONALE FOR THE PROJECT 1.2 BACKGROUND AND SCOPE 1.3 OBJECTIVES AND RESEARCH QUESTION 1.3.1 General objective 1.3.2 Specific objectives 1.4 DOCUMENT OUTLINE 1.5 DISSEMINATION AND EXPLOITATION 2 INFLUENCE OF CASHEW NUT SHELL LIQUID ON CORROSION AND TRIBOCORROSION BEHAVIOUR OF METALLIC ALLOYS 2.1 MATERIALS AND METHODS 2.2 RESULTS AND DISCUSSION 3 CORROSION AND TRIBOCORROSION PROTECTION OF MILD STEEL BY ORGANIC COATING FROM CASHEW NUT SHELL LIQUID 3.1 MATERIALS AND METHODS 3.2 RESULTS AND DISCUSSION 4 DISCUSSION 5 CONCLUSIONS BIBLIOGRAPHY ABREVIATIONS
Keywords: Corrosión en aleaciones - Pruebas; Aleaciones de metales ligeros; Aleaciones diluidas; Compuestos metálicos; Corrosión; Tribocorrosión; Cashee nut shell liquid; Lubrication; Coating; Metallic